Caracterização de sistemas varistores a base de SnO2-MnO2 - Orlandi, Marcelo Ornaghi (Universidade Federal de São Carlos, 2002)
This work focussed on the effect of addition of Nb2O5 on the electrical and microestructural properties of SnO2-MnO2 based ceramics. It was also studied the effect of heat-treatments in a oxygen-rich atmosphere in these properties. The parent system was 99,5% SnO2-0,5% MnO2 in molar ratio, a dense system that did not present non-ohmic behavior. The addition of Nb2O5 on this system promoted an increase on the charge carrier number in the SnO2 matrix and, then, varistor properties were observed. Otherwise, the upper doping level, 0.25% mol of Nb2O5 system showed an higher porosity, due to the decrease on the thermal sintering properties, that depleted the varistor characteristic of this system. A detailed study on the electrical properties were performed using impedance spectroscopy and the obtained results showed that Nb2O5 tends to form an electronic trapping level between the valence and the conduction bands, modifying the potential barrier properties formed in the grain boundaries region. In order to explain the obtained results, it was proposed a parallel equivalent circuit model, based on the grain boundaries contributions to electrical properties. Heat-treatments under oxygen-rich atmosphere did not changed the observed electrical properties in the systems, due to the presence of numerous secondary phases (rich in oxygen and manganese), localized in triple points in the grain boundaries. It is pointed the there is a oxygen local enrichment in these phases, not significantly altering the observed macroscopical electrical characteristics in the analyzed systems.
Characterization of varistors system s SnO2-MnO2 based
Keywords: Propriedades elétricas; Cerâmica; Dióxido de estanho; Espectroscopia de impedância; Atmosfera de oxigênio; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA